The Character of Ukraine in the Serbian Novel of the Second Half of the 20th – the Beginning of the 21st Century - Bilyk, Natalia (Poznańskie Studia Slawistyczne, 2022)
Traditionally, the basic qualities of imagology are associated with its key category—the literary ethnic character. A special field of imagological improvisations is the Serbian novel, which, according to well-known national experience and specific genre features, is favorable for ethnic panoramic imagological reactions, especially when it comes to the mid-20th – early 21st century. The aim of the research is to single out in chronological supposition the poetics of the literary presentation of the phenomenon of Ukraine in the Serbian novelistic discourse at the turn of the millennium. The research is based on comparative, comparative-typological, imagological methods in combination with approaches of structural-semantic and archetypal analysis. In the stated imagological perspective, the novels by I. Andrić, M. Crnjanski, M. Oljača, M. Selimović, G. Petrović, M. Prodanović and М. Pavić are analyzed. The works highlight semantic accents that emphasize the positive imagological view of Ukraine from its foreign ethnic reception, formed in genetically related – Serbian – literature, the tolerance of the Serbian people in creating subjective ethnic panoramas, indispensable for the evolutionary enrichment of intercultural communication based on epistemological heritage.